The Abbasid Revolution and its Aftermath in the Chronicle of Theophanes the Confessor. Part Two - Cecota, Błażej Andrzej (Balcanica Posnaniensia. Acta et studia, 2023)
In the first part of my article, I described how Theophanes the Confessor refused to legitimize the Abbasids, recognizing the legitimacy of Umayyad rule (according to the chronicler, the Umayyad power came directly from the Prophet Muhammad, which is obviously not entirely true). The chronograph emphasized that the Abbasids used the lower classes to seize power, which allowed them to lead to a state of anarchy. At the same time, he noticed how bad a ruler Marwan the Second was. From this difficult situation, as can be understood, there was no good way out, because both sides of the dispute were tainted with sins that led to injustice or unrighteousness. This was confirmed by supernatural phenomena mentioned by historian in the context of the change of power in the Muslim state. In the second part of my paper, I described how Theophanes tried to suggest that the Abbasid rule had led to religious and class divisions in the country. As a chronicler described the manifestations of anarchy that led to the persecution of Christians in Muslim countries. According to my interpretation, the description of the civil war in the caliphate after the death of Harun ar-Rashid in the work of Theophanes the Confessor is almost a harbinger of the end of the Muslim empire.